Práticas discursivas de professores de Matemática na condução de discussões coletivas - Rodrigues, Cátia (2020)
Mathematical discussions are a tool within the reach of the teacher to promote communication in the mathematics class, as students are asked to present their resolution strategies, to compare them with those of their peers, to justify and argue about the mobilized reasoning in these solutions of a task proposed by the teacher. When class discourse focuses on algebraic ideas, symbolization and generalization are enhanced, as students are encouraged to use increasingly formal language and broaden their thinking beyond the considered cases. This qualitative and interpretative study seeks to understand how three teachers of mathematics in the 3rd cycle of basic education manage and promote discourse during a collective discussion with mathematical tasks with a view to teaching Algebra. The results show that teachers, supported by the teaching actions of eliciting, supporting, informing, and challenging, direct the discourse through a cyclical process of requesting and discussing many ideas and of filtering, seeking to lead students to relate, generalize and justify algebraic ideas.